A method for preparing methanol by hydrogenating carbon dioxide

By modifying the catalyst filler composed of molybdenum disulfide, indium-containing co-precipitated metal and porous carbon powder, the problem of low activity and selectivity of the catalyst for hydrogenation of carbon dioxide to produce methanol in the prior art is solved, and a higher carbon dioxide conversion rate is achieved and methanol selectivity.

CN119143576BActive Publication Date: 2025-02-11ANHUI CARBON XIN TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411654179.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-11
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

In the prior art, the activity and selectivity of the methanol catalyst for hydrogenation of carbon dioxide are not high, resulting in the increase in carbon dioxide conversion and methanol selectivity.

Method used

The catalyst filler composed of modified molybdenum disulfide, indium-containing co-precipitated metal and porous carbon powder is used to improve the specific surface area and porosity of the catalyst through chemical modification and solization granulation and post-calcination molding, thereby optimizing the catalytic reaction path.

Benefits of technology

The selectivity and conversion rate of methanol prepared by hydrogenation of carbon dioxide are significantly improved, and the activity and mass transfer properties of the catalyst are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_13
    Figure SMS_13
Patent Text Reader

Abstract

The invention discloses a method for preparing methanol by hydrogenating carbon dioxide, belongs to the technical field of carbon dioxide hydrogenation, and is used to solve the technical problem that in the process of preparing methanol by hydrogenating carbon dioxide in the prior art, the conversion rate of catalyst filler for catalytic carbon dioxide conversion and the selectivity of conversion to methanol need to be further improved. The invention comprises the following steps: carbon dioxide and hydrogen are mixed and compressed to obtain a compressed mixed gas, and the catalyst filler is filled into a methanol synthesis tower. The invention optimizes the preparation of modified molybdenum disulfide, indium-containing coprecipitated metal and porous carbon powder, and coats and modifies them, so as to effectively improve the specific surface area and porosity of the catalyst filler, and also improve the conversion rate of carbon dioxide and the selectivity of conversion to methanol of the catalyst filler in the process of preparing methanol by hydrogenating carbon dioxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon dioxide hydrogenation, and in particular to a method for preparing methanol by hydrogenating carbon dioxide. Background Art

[0002] As the global warming problem becomes increasingly serious, reducing greenhouse gas emissions, especially carbon dioxide emissions, has become an important task for countries around the world. The burning of fossil fuels produces a large amount of CO 2 , these CO 2 Most of it is not absorbed naturally but enters the atmosphere, causing the greenhouse effect to intensify;

[0003] To address this challenge, CO 2 In addition to capture and storage technologies, CO 2 Converting carbon dioxide into valuable chemicals and fuels is an important way to realize its resource utilization. Catalytic hydrogenation of carbon dioxide into methanol not only helps to reduce greenhouse gas emissions, but also provides valuable fuels and chemicals, promoting the optimization of energy structure and sustainable development.

[0004] The prior art, a Chinese invention patent with publication number CN110833843A, discloses a catalyst for synthesizing methanol by hydrogenating carbon dioxide, which mainly solves the problem of low activity and selectivity of the catalyst for synthesizing methanol by hydrogenating carbon dioxide in the prior art, and uses molybdenum disulfide as the main component of the catalyst for synthesizing methanol by hydrogenating carbon dioxide. The catalyst for synthesizing methanol by hydrogenating carbon dioxide has the characteristics of low price, simple operation, high carbon dioxide conversion rate, high methanol selectivity in the product, good stability, etc.

[0005] The above patent content is to use molybdenum disulfide as a catalyst to catalyze the hydrogenation of carbon dioxide to produce methanol. However, the process of hydrogenating carbon dioxide to produce methanol involves the diffusion and mass transfer of gas in the solid catalyst. Traditional catalysts are usually mixed with carriers by simple physical methods to form a load. The active sites on the surface of the catalyst are easily coated by the carrier, which reduces the mass transfer effect between the gas and the active catalytic sites of the catalyst, resulting in the catalyst filler The conversion rate of carbon dioxide and the selectivity for methanol conversion in the catalytic hydrogenation of carbon dioxide to produce methanol need to be further improved.

[0006] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0007] The object of the present invention is to provide a method for preparing methanol by hydrogenating carbon dioxide, which is used to solve the technical problem that in the process of preparing methanol by hydrogenating carbon dioxide in the prior art, the conversion rate of catalyst fillers for catalytic carbon dioxide conversion and its selectivity for conversion to methanol need to be further improved.

[0008] The object of the present invention can be achieved by the following technical scheme: A method for preparing methanol by hydrogenating carbon dioxide comprises the following steps:

[0009] S1, mixing carbon dioxide and hydrogen and compressing them to obtain a compressed mixed gas;

[0010] S2, filling the catalyst filler into the methanol synthesis tower; the compressed mixed gas is heated and then transported to the methanol synthesis tower, and after catalytic synthesis, it is discharged from the top of the methanol synthesis tower to obtain synthesis gas, wherein the catalyst filler is based on a mixed powder composed of modified molybdenum disulfide, indium-containing co-precipitated metal and porous carbon powder, which is obtained by chemical modification and sol granulation, and then calcined and formed;

[0011] S3, after heat exchange and cooling, the synthesis gas enters the separator to separate methanol and water in the mixed gas to obtain crude alcohol and recovered gas, which is then compressed and mixed with the compressed mixed gas for recycling;

[0012] S4. The crude alcohol is transported to a distillation tower for distillation to obtain methanol and production waste liquid.

[0013] Furthermore, in step S1, the volume ratio of carbon dioxide to hydrogen is 1:4-6; in step S2, the temperature of the methanol synthesis tower is 280-320°C and the pressure is 2-6 bar; in step S3, the temperature of the synthesis gas after heat exchange and cooling is 5-15°C; in step S4, the temperature of the distillation tower is 70-80°C and the pressure is 0.1-0.6 bar.

[0014] Further, the catalyst filler is processed by the following steps:

[0015] A1. Add modified molybdenum disulfide, indium-containing co-precipitated metal and porous carbon powder into a ball mill, and pass through a 200-mesh sieve after ball milling to obtain a mixed powder;

[0016] A2, adding the mixed powder and emulsion into a reactor, stirring for 30-50 min, adding phloroglucinol, formaldehyde solution, ethyl orthosilicate and ammonia water into the reactor, raising the temperature of the reactor to 55-65°C, keeping the temperature for 20-22h, and post-treating to obtain a modified mixed powder;

[0017] The synthetic reaction mechanism of the modified mixed powder is:

[0018] Under alkaline conditions, phloroglucinol and formaldehyde undergo a condensation reaction to form a phenolic resin-like organic substance, and tetraethyl orthosilicate is hydrolyzed and condensed under alkaline conditions to form a silicon dioxide network structure, which serves as an inorganic reinforcing phase and forms a modified coating layer with a mutually reinforced cross-linked network structure on the surface of the mixed powder particles with the phenolic resin to prepare a modified mixed powder.

[0019] A3, adding the modified mixed powder, sodium aluminate, silica sol, starch, dispersant and deionized water into a reactor, stirring and dispersing at room temperature for 20-30 minutes, adding the sodium alginate solution into the reactor, stirring at this temperature for 20-30 minutes, and obtaining a mixed solution;

[0020] A4. The mixed liquid is granulated and solidified to obtain a catalyst filler.

[0021] Furthermore, in step A1, the weight ratio of the modified molybdenum disulfide, the indium-containing co-precipitated metal and the porous carbon powder is 5-7:2-3:6-8; in step A2, the amount ratio of the mixed powder, the emulsion, phloroglucinol, the formaldehyde solution, tetraethyl orthosilicate and the ammonia water is 10g:200mL:5g:10g:30-40g:2-3g:6-8mL, the emulsion is composed of anhydrous ethanol, purified water, hexadecyltrimethylammonium bromide and polyethylene glycol 200 in a dosage ratio of 50mL:30mL:3g:1g, the mass content of the formaldehyde solution is 28-35%, and the mass content of the ammonia water is 15-2 5%, the post-treatment includes: after the reaction is completed, centrifuging, washing the solid with anhydrous ethanol and deionized water for 3 times and then drying, transferring the solid to a drying oven at a temperature of 70-80°C, and vacuum drying to constant weight to obtain a modified mixed powder; in step A3, the amount ratio of the modified mixed powder, sodium aluminate, silica sol, starch, dispersant, deionized water and sodium alginate solution is 5g:4-6g:60-70g:12-15g:2-3g:200mL:40mL, the dispersant is sodium dodecyl sulfate, and the sodium alginate solution is composed of sodium alginate and deionized water in a ratio of 1g:50mL.

[0022] Further, in step A4, granulation and curing comprises the following steps:

[0023] B1, adding the mixed solution dropwise to the calcium chloride solution, curing for 60-80 minutes, and post-processing to obtain a catalyst filler body;

[0024] The synthesis reaction mechanism of the catalyst filler body is:

[0025] In a mixture consisting of modified mixed powder, sodium aluminate, silica sol, starch, dispersant and deionized water, after the mixture is added dropwise into a calcium chloride solution, the sodium alginate molecules therein rapidly chelate with the calcium chloride ions to form a gel, and at the same time other components in the mixture are also wrapped in the gel. The gel solidifies in the calcium chloride solution for a period of time to form a microsphere-like solid, thereby obtaining a catalyst filler blank.

[0026] B2. Place the catalyst filler blank in a nitrogen-protected tubular furnace, and perform calcination in the tubular furnace according to a procedure to obtain the catalyst filler.

[0027] The synthesis reaction mechanism of the catalyst filler is:

[0028] The catalyst filler is prepared by gradually removing moisture and volatile organic matter in the catalyst filler blank through programmed calcination, promoting the optimization of the crystallization and pore structure of the catalyst filler.

[0029] Furthermore, in step B1, the concentration of the calcium chloride solution is 0.2-0.3 mol / L, and the post-treatment includes: after the reaction is completed, filtering, washing the filter cake with purified water for 3 times and then draining, transferring the filter cake to a drying oven at a temperature of 70-80°C, and drying to constant weight to obtain a catalyst filler blank; in step B2, the process of programmed calcination is: the temperature of the tubular furnace is increased to 110-120°C at a heating rate of 5-8°C / min, and the temperature is kept for 30-50min, the temperature of the tubular furnace is increased to 220-260°C at a heating rate of 2-4°C / min, and the temperature is kept for 40-60min, and the temperature of the tubular furnace is increased to 430-450°C at a heating rate of 3-5°C / min, and the temperature is kept for 50-60min, and the temperature is naturally reduced to room temperature.

[0030] Furthermore, the preparation method of modified molybdenum disulfide is: adding ammonium molybdate, thiourea and deionized water into a reactor and stirring, raising the temperature of the reactor to reflux the system, adding copper acetate solution to the reactor, keeping the temperature for reaction for 22-24 hours, and post-treating to obtain modified molybdenum disulfide.

[0031] The synthetic reaction mechanism of modified molybdenum disulfide is:

[0032] In the reactor process, ammonium molybdate provides a molybdenum source, and thiourea serves as a sulfur source. At high temperature, thiourea decomposes to produce hydrogen sulfide, which reacts with molybdate ions to form a precursor of molybdenum disulfide. At the same time, copper ions react with thiourea to form copper-containing sulfides or complexes as modifiers, which are embedded in the crystal lattice of molybdenum disulfide to obtain molybdenum disulfide.

[0033] Furthermore, the dosage ratio of the ammonium molybdate, thiourea, deionized water and copper acetate solution is 1g:4g:25mL:3g, the copper acetate solution is composed of copper acetate and deionized water in a weight ratio of 1:4, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with deionized water for 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 80-90°C, and vacuum dried to constant weight to obtain modified molybdenum disulfide.

[0034] Furthermore, the preparation method of the indium-containing co-precipitated metal is as follows: zinc nitrate, indium nitrate and deionized water are added to a reactor and stirred until the system is dissolved, sodium carbonate solution is added dropwise to the reactor, the pH of the system is adjusted to 8.8-9.2, the temperature of the reactor is increased to 70-75°C, and the mixture is stirred for 3-5 hours at a temperature maintained at room temperature, the temperature of the reactor is decreased to 45-55°C, and the mixture is aged for 6-8 hours at a temperature maintained at room temperature, and the indium-containing co-precipitated metal is obtained by post-treatment.

[0035] The synthesis reaction mechanism of indium-containing co-precipitated metals is:

[0036] Zinc nitrate and indium nitrate are dissolved in water to form an aqueous solution of zinc ions and indium ions. Sodium carbonate is ionized in water to produce carbonate ions. The carbonate ions react with zinc ions and indium ions to form corresponding carbonate precipitates. These precipitates gradually grow and stabilize during the reaction and aging process to obtain indium-containing co-precipitated metals.

[0037] Furthermore, the dosage ratio of the zinc nitrate, indium nitrate and deionized water is 1g:3g:50mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the filter cake is filtered, the filter cake is washed with purified water for 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 90-100°C, and dried to constant weight to obtain an indium-containing co-precipitated metal.

[0038] Further, the porous carbon powder is processed by the following steps:

[0039] C1. Add nicotinic acid solution and chitosan into a reactor and stir. Raise the temperature of the reactor to 60-70°C, keep warm and stir for 10-12h, and perform post-treatment to obtain modified chitosan.

[0040] C2, placing the modified chitosan mixture in a nitrogen-protected tubular furnace, raising the temperature of the tubular furnace to 600-650°C, maintaining the temperature for 120-160 minutes, cooling and discharging the material to obtain a porous carbon powder crude product;

[0041] C3. Add the crude porous carbon powder and the activation solution into a reactor, stir at room temperature for 6-8 hours, and perform post-treatment to obtain porous carbon powder.

[0042] The synthetic reaction mechanism of porous carbon powder is:

[0043] Chitosan is a natural polymer rich in amino groups. It is mixed with nicotinic acid solution as a carbon source and a nitrogen source, and is kept warm and stirred at a certain temperature. The amino groups on the chitosan react with nicotinic acid or its hydrolysis product to introduce nitrogen elements. Zinc chloride is evenly dispersed in the chitosan as a template. In an inert gas and high temperature environment, the modified chitosan is fully pyrolyzed and carbonized to form a crude porous carbon powder. After washing and etching with a hydrochloric acid solution, the zinc chloride on the crude porous carbon powder particles is washed away to form a porous carbon powder.

[0044] Furthermore, in step C1, the amount ratio of chitosan to nicotinic acid solution is 1g:20mL, the nicotinic acid solution is composed of nicotinic acid, zinc chloride and deionized water in an amount ratio of 1g:5g:30mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is increased to 70-80°C, and the solvent is evaporated under reduced pressure to obtain modified chitosan; in step C3, the amount ratio of the porous carbon powder crude product to the activation solution is 1g:30-50mL, and the activation solution is 0.8-1.2mol / L hydrochloric acid. The post-treatment includes: after the reaction is completed, suction filtration, washing the filter cake with deionized water until neutral and then drying, transferring the filter cake to a drying oven at a temperature of 70-80°C, and vacuum drying to constant weight to obtain porous carbon powder.

[0045] The present invention has the following beneficial effects:

[0046] 1. The preparation method of the catalyst filler for preparing methanol by hydrogenation of carbon dioxide in the present application, the sulfur vacancies on the molybdenum disulfide molecules are confirmed to be the catalytic CO 2 Highly selective hydrogenation to the active center of methanol can promote the MoS 2 The formation of sulfur vacancies in the basal plane and the reaction of Cu ions with acidic CO 2 There is a strong acid-base interaction between the molecules, which enhances the catalyst's CO 2 Due to the difference in radius between zinc ions and indium ions, the lattice will be distorted to a certain extent, and the introduction of zinc ions may produce new active sites. When located at the lattice distortion, the coordination environment of zinc ions and surrounding atoms is CO 2 and H 2 The conversion of CO provides more opportunities by cooperating with modified MoS2 and co-precipitated metals containing indium to make more CO 2 and H 2 It is possible to optimize CO while efficiently converting at these sites. 2 The hydrogenation reaction pathway makes the production of methanol easier and improves the selectivity of producing methanol by hydrogenation of carbon dioxide.

[0047] 2. The preparation method of the catalyst filler for preparing methanol by hydrogenation of carbon dioxide of the present application is to mix nitrogen-doped porous carbon powder with modified molybdenum dioxide and indium-containing co-precipitated metal. The porous carbon powder itself has a rich pore structure and can contribute to a higher porosity. Nitrogen atoms are introduced into the carbon powder to break the original arrangement of carbon atoms, form more surface defects and unevenness on the porous carbon powder, and increase the specific surface area of ​​the porous carbon powder. Nitrogen atoms have lone pairs of electrons that can react with CO 2 or H 2The molecules interact with each other to form a stable adsorption state, which is beneficial to the adsorption and activation of reactants, reduces the activation energy of the reaction, and improves the catalytic efficiency. The introduction of nitrogen atoms may break the original arrangement of carbon atoms and form new chemical bonds and functional groups. These changes may lead to fine-tuning of the pore structure, making the pores that may have been blocked or narrow become more open. The open pore structure and enhanced connectivity provide more diffusion channels for reactant molecules. These channels enable fast-diffusing reactant molecules to more easily enter the pores and come into contact with the active sites of the catalyst, thereby further increasing the rate of the catalytic reaction.

[0048] 3. The preparation method of the catalyst filler for preparing methanol by hydrogenation of carbon dioxide of the present application comprises the following steps: coating the outside of the mixed powder particles with a coating layer of polysiloxane-reinforced phenolic resin, using corn starch and sodium dodecyl sulfate as dispersants and surfactants, which help to evenly disperse the particles in the mixed liquid and prevent agglomeration. In a high temperature environment, sodium aluminate and silica sol are used as inorganic structural additives to promote the formation and stability of the catalyst filler structure in a high temperature environment. Moreover, in a high temperature environment, the organic matter and starch on the coating layer on the surface of the mixed powder are gradually carbonized to form a catalyst filler with a porous structure, thereby increasing the specific surface area of ​​the catalyst filler. A high specific surface area means more catalytic active sites, which is beneficial to improving the rate and mass transfer performance of the catalytic reaction, and making it easier for the reactant molecules to reach the catalytic active sites and react. DETAILED DESCRIPTION

[0049] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] The silica sol in this application is selected from Guangzhou Jinkai Chemical Co., Ltd., the model is Grace HS-40, the density is 1.3g / cm³, and the average particle size is 12nm.

[0051] Example 1

[0052] This embodiment provides a method for preparing a catalyst filler for preparing methanol by hydrogenating carbon dioxide, comprising the following steps:

[0053] S1. Preparation of modified molybdenum disulfide

[0054] Copper acetate and deionized water are mixed uniformly in a weight ratio of 1:4 to obtain a copper acetate solution;

[0055] Weigh: 100 g of ammonium molybdate, 400 g of thiourea and 2500 mL of deionized water, add them into a reactor and stir, raise the temperature of the reactor to reflux the system, add 300 g of copper acetate solution into the reactor, keep the reaction for 22 hours, lower the temperature of the reactor to room temperature, filter, wash the filter cake with deionized water 3 times and then drain, transfer the filter cake to a drying oven at a temperature of 80°C, and vacuum dry it to constant weight to obtain modified molybdenum disulfide.

[0056] S2. Preparation of indium-containing co-precipitated metal

[0057] Weigh: 100 g zinc nitrate, 300 g indium nitrate and 5000 mL deionized water, add to the reactor and stir until the system is dissolved, add 3 mol / L sodium carbonate solution dropwise to the reactor, adjust the system pH to 8.8, raise the reactor temperature to 70°C, keep stirring for 3 hours, lower the reactor temperature to 45°C, keep aging for 6 hours, lower the reactor temperature to room temperature, filter, wash the filter cake 3 times with purified water and then drain, transfer the filter cake to a drying oven at 90°C, dry to constant weight, and obtain indium-containing co-precipitated metal.

[0058] S3. Preparation of porous carbon powder

[0059] Nicotinic acid, zinc chloride and deionized water were mixed uniformly in a dosage ratio of 1 g:5 g:30 mL to obtain a nicotinic acid solution;

[0060] Weigh: 1000 mL of nicotinic acid solution and 50 g of chitosan are added to a reactor and stirred. The temperature of the reactor is raised to 60° C. and stirred for 10 h. The temperature of the reactor is raised to 70° C. and the solvent is evaporated under reduced pressure to obtain modified chitosan.

[0061] The modified chitosan mixture was placed in a nitrogen-protected tubular furnace, the temperature of the tubular furnace was raised to 600°C, the temperature was kept for 120 minutes, and the material was cooled and discharged to obtain a porous carbon powder crude product;

[0062] The crude porous carbon powder and 0.8 mol / L hydrochloric acid were added into a reactor at a dosage ratio of 1 g:30 mL, stirred at room temperature for 6 h, filtered, the filter cake was washed with deionized water until neutral and then dried, the filter cake was transferred to a drying oven at a temperature of 70°C, and vacuum dried to constant weight to obtain porous carbon powder.

[0063] S4. Preparation of modified mixed powder

[0064] Weigh: modified molybdenum disulfide, indium-containing co-precipitated metal and porous carbon powder are added into a ball mill in a weight ratio of 5:2:6, and after ball milling, the mixture is passed through a 200-mesh sieve to obtain a mixed powder;

[0065] Anhydrous ethanol, purified water, hexadecyltrimethylammonium bromide and polyethylene glycol 200 were uniformly mixed in a dosage ratio of 50 mL:30 mL:3 g:1 g to obtain an emulsion;

[0066] Weigh: 200 g of mixed powder and 4000 mL of emulsion are added to the reactor and stirred for 30 min. 100 g of phloroglucinol, 600 g of 28 wt% formaldehyde solution, 40 g of tetraethyl orthosilicate and 120 mL of 15 wt% ammonia water are added to the reactor. The temperature of the reactor is raised to 55°C and kept warm for 20 h. The temperature of the reactor is lowered to room temperature and centrifuged. The solid is washed three times with anhydrous ethanol and deionized water respectively and then dried. The solid is transferred to a drying oven at a temperature of 70°C and vacuum dried to constant weight to obtain a modified mixed powder.

[0067] S5. Preparation of catalyst filler

[0068] Sodium alginate and deionized water were mixed evenly at a dosage ratio of 1 g:50 mL to obtain a sodium alginate solution;

[0069] Weigh: 200 g of modified mixed powder, 160 g of sodium aluminate, 2400 g of silica sol, 480 g of corn starch, 80 g of sodium dodecyl sulfate and 8000 mL of deionized water, add them into a reactor, stir and disperse at room temperature for 20 min, add 1600 mL of sodium alginate solution into the reactor, keep warm and stir for 20 min to obtain a mixed solution;

[0070] The mixed solution was added dropwise into 10L 0.2mol / L calcium chloride solution, solidified for 60min, filtered, the filter cake was washed with purified water for 3 times and then dried, and the filter cake was transferred to a drying oven at 70°C and dried to constant weight to obtain a catalyst filler body;

[0071] The catalyst filler blank was placed in a nitrogen-protected tubular furnace, and the temperature of the tubular furnace was increased to 110°C at a heating rate of 5°C / min and kept warm for 30 minutes. The temperature of the tubular furnace was increased to 220°C at a heating rate of 2°C / min and kept warm for 40 minutes. The temperature of the tubular furnace was further increased to 430°C at a heating rate of 3°C / min, and the temperature was kept warm for 50 minutes. The catalyst filler was naturally cooled to room temperature and discharged to obtain the catalyst filler.

[0072] Example 2

[0073] This embodiment provides a method for preparing a catalyst filler for preparing methanol by hydrogenating carbon dioxide, comprising the following steps:

[0074] S1. Preparation of modified molybdenum disulfide

[0075] Copper acetate and deionized water are mixed uniformly in a weight ratio of 1:4 to obtain a copper acetate solution;

[0076] Weigh: 100 g of ammonium molybdate, 400 g of thiourea and 2500 mL of deionized water, add them into a reactor and stir, raise the temperature of the reactor to reflux the system, add 300 g of copper acetate solution into the reactor, keep the reaction for 23 hours, lower the temperature of the reactor to room temperature, filter, wash the filter cake with deionized water 3 times and then drain, transfer the filter cake to a drying oven at a temperature of 85°C, and vacuum dry it to constant weight to obtain modified molybdenum disulfide.

[0077] S2. Preparation of indium-containing co-precipitated metal

[0078] Weigh: 100 g zinc nitrate, 300 g indium nitrate and 5000 mL deionized water, add to the reactor and stir until the system is dissolved, add 4 mol / L sodium carbonate solution dropwise to the reactor, adjust the system pH to 9.0, raise the reactor temperature to 73°C, keep stirring for 4 hours, lower the reactor temperature to 50°C, keep aging for 7 hours, lower the reactor temperature to room temperature, filter, wash the filter cake with purified water 3 times and then drain, transfer the filter cake to a drying oven at 95°C, dry to constant weight, and obtain indium-containing co-precipitated metal.

[0079] S3. Preparation of porous carbon powder

[0080] Nicotinic acid, zinc chloride and deionized water were mixed uniformly in a dosage ratio of 1 g:5 g:30 mL to obtain a nicotinic acid solution;

[0081] Weigh: 1000 mL of nicotinic acid solution and 50 g of chitosan are added to a reactor and stirred. The temperature of the reactor is raised to 65° C. and stirred for 11 hours. The temperature of the reactor is raised to 75° C. and the solvent is evaporated under reduced pressure to obtain modified chitosan.

[0082] The modified chitosan mixture was placed in a nitrogen-protected tubular furnace, the temperature of the tubular furnace was raised to 625°C, the temperature was kept for 140 minutes, and the material was cooled and discharged to obtain a porous carbon powder crude product;

[0083] The crude porous carbon powder and 1.0 mol / L hydrochloric acid were added into a reactor at a dosage ratio of 1 g:40 mL, stirred at room temperature for 7 h, filtered, the filter cake was washed with deionized water until neutral and then dried, the filter cake was transferred to a drying oven at a temperature of 75°C, and vacuum dried to constant weight to obtain porous carbon powder.

[0084] S4. Preparation of modified mixed powder

[0085] Weigh: modified molybdenum disulfide, indium-containing co-precipitated metal and porous carbon powder are added into a ball mill in a weight ratio of 6:2.5:7, and after ball milling, the mixture is passed through a 200-mesh sieve to obtain a mixed powder;

[0086] Anhydrous ethanol, purified water, hexadecyltrimethylammonium bromide and polyethylene glycol 200 were uniformly mixed in a dosage ratio of 50 mL:30 mL:3 g:1 g to obtain an emulsion;

[0087] Weigh: 200 g of mixed powder and 4000 mL of emulsion are added to the reactor and stirred for 40 min. 100 g of phloroglucinol, 700 g of 31 wt% formaldehyde solution, 50 g of tetraethyl orthosilicate and 140 mL of 20 wt% ammonia water are added to the reactor. The temperature of the reactor is raised to 60°C and kept warm for 21 hours. The temperature of the reactor is lowered to room temperature and centrifuged. The solid is washed three times with anhydrous ethanol and deionized water respectively and then dried. The solid is transferred to a drying oven at a temperature of 75°C and vacuum dried to constant weight to obtain a modified mixed powder.

[0088] S5. Preparation of catalyst filler

[0089] Sodium alginate and deionized water were mixed evenly at a dosage ratio of 1 g:50 mL to obtain a sodium alginate solution;

[0090] Weigh: 200 g of modified mixed powder, 200 g of sodium aluminate, 2600 g of silica sol, 540 g of corn starch, 100 g of sodium dodecyl sulfate and 8000 mL of deionized water, add them into a reactor, stir and disperse them at room temperature for 25 min, add 1600 mL of sodium alginate solution into the reactor, keep warm and stir for 25 min to obtain a mixed solution;

[0091] The mixed solution was added dropwise into 10L 0.25mol / L calcium chloride solution, solidified for 70min, filtered, the filter cake was washed with purified water for 3 times and then dried, and the filter cake was transferred to a drying oven at 75°C and dried to constant weight to obtain a catalyst filler body;

[0092] The catalyst filler blank was placed in a nitrogen-protected tubular furnace, and the temperature of the tubular furnace was increased to 115°C at a heating rate of 7°C / min, and kept warm for 40 minutes. The temperature of the tubular furnace was increased to 240°C at a heating rate of 3°C / min, and kept warm for 50 minutes. The temperature of the tubular furnace was further increased to 440°C at a heating rate of 4°C / min, and the temperature was kept warm for calcination for 55 minutes. The temperature was naturally cooled to room temperature, and the material was discharged to obtain the catalyst filler.

[0093] Example 3

[0094] This embodiment provides a method for preparing a catalyst filler for preparing methanol by hydrogenating carbon dioxide, comprising the following steps:

[0095] S1. Preparation of modified molybdenum disulfide

[0096] Copper acetate and deionized water are mixed uniformly in a weight ratio of 1:4 to obtain a copper acetate solution;

[0097] Weigh: 100 g of ammonium molybdate, 400 g of thiourea and 2500 mL of deionized water, add them into a reactor and stir, raise the temperature of the reactor to reflux the system, add 300 g of copper acetate solution into the reactor, keep the reaction for 24 hours, lower the temperature of the reactor to room temperature, filter, wash the filter cake with deionized water 3 times and then drain, transfer the filter cake to a drying oven at a temperature of 90° C., and vacuum dry it to constant weight to obtain modified molybdenum disulfide.

[0098] S2. Preparation of indium-containing co-precipitated metal

[0099] Weigh: 100 g zinc nitrate, 300 g indium nitrate and 5000 mL deionized water, add to the reactor and stir until the system is dissolved, add 5 mol / L sodium carbonate solution dropwise to the reactor, adjust the system pH to 9.2, raise the reactor temperature to 75°C, keep stirring for 5 hours, lower the reactor temperature to 55°C, keep aging for 8 hours, lower the reactor temperature to room temperature, filter, wash the filter cake with purified water 3 times and then drain, transfer the filter cake to a drying oven at 100°C, dry to constant weight, and obtain indium-containing co-precipitated metal.

[0100] S3. Preparation of porous carbon powder

[0101] Nicotinic acid, zinc chloride and deionized water were mixed uniformly in a dosage ratio of 1 g:5 g:30 mL to obtain a nicotinic acid solution;

[0102] Weigh: 1000 mL of nicotinic acid solution and 50 g of chitosan are added to a reactor and stirred. The temperature of the reactor is raised to 70° C. and stirred for 12 h. The temperature of the reactor is raised to 80° C. and the solvent is evaporated under reduced pressure to obtain modified chitosan.

[0103] The modified chitosan mixture was placed in a nitrogen-protected tubular furnace, the temperature of the tubular furnace was raised to 650°C, the temperature was kept for 160 minutes, and the material was cooled and discharged to obtain a porous carbon powder crude product;

[0104] The crude porous carbon powder and 1.2 mol / L hydrochloric acid were added into a reactor at a dosage ratio of 1 g:50 mL, stirred at room temperature for 8 h, filtered, the filter cake was washed with deionized water until neutral and then dried, the filter cake was transferred to a drying oven at 80°C, and vacuum dried to constant weight to obtain porous carbon powder.

[0105] S4. Preparation of modified mixed powder

[0106] Weigh: modified molybdenum disulfide, indium-containing co-precipitated metal and porous carbon powder are added into a ball mill in a weight ratio of 7:3:8, and after ball milling, the mixture is passed through a 200-mesh sieve to obtain a mixed powder;

[0107] Anhydrous ethanol, purified water, hexadecyltrimethylammonium bromide and polyethylene glycol 200 were uniformly mixed in a dosage ratio of 50 mL:30 mL:3 g:1 g to obtain an emulsion;

[0108] Weigh: 200 g of mixed powder and 4000 mL of emulsion are added to the reactor and stirred for 50 min. 100 g of phloroglucinol, 800 g of 35 wt% formaldehyde solution, 60 g of tetraethyl orthosilicate and 160 mL of 25 wt% ammonia water are added to the reactor. The temperature of the reactor is raised to 65°C and kept warm for 22 h. The temperature of the reactor is lowered to room temperature and centrifuged. The solid is washed three times with anhydrous ethanol and deionized water respectively and then dried. The solid is transferred to a drying oven at 80°C and vacuum dried to constant weight to obtain a modified mixed powder.

[0109] S5. Preparation of catalyst filler

[0110] Sodium alginate and deionized water were mixed evenly at a dosage ratio of 1 g:50 mL to obtain a sodium alginate solution;

[0111] Weigh: 200 g of modified mixed powder, 240 g of sodium aluminate, 2800 g of silica sol, 600 g of corn starch, 120 g of sodium dodecyl sulfate and 8000 mL of deionized water, add them into a reactor, stir and disperse them at room temperature for 30 min, add 1600 mL of sodium alginate solution into the reactor, keep warm and stir for 30 min to obtain a mixed solution;

[0112] The mixed solution was added dropwise into 10L 0.3mol / L calcium chloride solution, solidified for 80min, filtered, the filter cake was washed with purified water for 3 times and then dried, and the filter cake was transferred to a drying oven at 80°C and dried to constant weight to obtain a catalyst filler body;

[0113] The catalyst filler blank was placed in a nitrogen-protected tubular furnace, and the temperature of the tubular furnace was increased to 120°C at a heating rate of 8°C / min, and kept warm for 50 minutes. The temperature of the tubular furnace was increased to 260°C at a heating rate of 4°C / min, and kept warm for 60 minutes. The temperature of the tubular furnace was further increased to 450°C at a heating rate of 5°C / min, and the temperature was kept warm for calcination for 60 minutes. The catalyst filler was naturally cooled to room temperature, discharged, and the catalyst filler was obtained.

[0114] Example 4

[0115] This embodiment provides a method for preparing methanol by hydrogenating carbon dioxide, comprising the following steps:

[0116] Step 1: mixing carbon dioxide and hydrogen in a volume ratio of 1:4 and compressing them to obtain a compressed mixed gas;

[0117] Step 2: Fill the catalyst filler prepared in Example 1 into a methanol synthesis tower, raise the temperature of the methanol synthesis tower to 280° C., and set the pressure to 2 bar; after the compressed mixed gas is heated to 90° C., it is transported to the methanol synthesis tower, and after catalytic synthesis, it is discharged from the top of the methanol synthesis tower to obtain synthesis gas;

[0118] Step 3: After heat exchange, the synthesis gas is cooled to 5°C and then enters the separator to separate methanol and water in the mixed gas to obtain crude alcohol and recovered gas. The recovered gas is compressed and then mixed with the compressed mixed gas through a pipeline for recycling;

[0119] Step 4: The crude alcohol is transported to a distillation tower at a temperature of 70° C. and a pressure of 0.1 bar for distillation to obtain methanol and production waste liquid.

[0120] Example 5

[0121] This embodiment provides a method for preparing methanol by hydrogenating carbon dioxide, comprising the following steps:

[0122] Step 1: mixing carbon dioxide and hydrogen in a volume ratio of 1:5 and compressing them to obtain a compressed mixed gas;

[0123] Step 2: Fill the catalyst filler prepared in Example 2 into a methanol synthesis tower, raise the temperature of the methanol synthesis tower to 300° C., and set the pressure to 4 bar; after heating the compressed mixed gas to 98° C., transport it to the methanol synthesis tower, and after catalytic synthesis, discharge it from the top of the methanol synthesis tower to obtain synthesis gas;

[0124] Step 3: After heat exchange, the synthesis gas is cooled to 10°C and then enters the separator to separate methanol and water in the mixed gas to obtain crude alcohol and recovered gas. The recovered gas is compressed and then mixed with the compressed mixed gas through a pipeline for recycling;

[0125] Step 4: The crude alcohol is transported to a distillation tower at a refining temperature of 75° C. and a pressure of 0.35 bar, and distilled to obtain methanol and production waste liquid.

[0126] Example 6

[0127] This embodiment provides a method for preparing methanol by hydrogenating carbon dioxide, comprising the following steps:

[0128] Step 1: mixing carbon dioxide and hydrogen in a volume ratio of 1:6 and compressing them to obtain a compressed mixed gas;

[0129] Step 2: Fill the catalyst filler prepared in Example 3 into a methanol synthesis tower, raise the temperature of the methanol synthesis tower to 320° C., and set the pressure to 6 bar; after the compressed mixed gas is heated to 105° C., it is transported to the methanol synthesis tower, and after catalytic synthesis, it is discharged from the top of the methanol synthesis tower to obtain synthesis gas;

[0130] Step 3: After heat exchange, the synthesis gas is cooled to 15°C and then enters the separator to separate methanol and water in the mixed gas to obtain crude alcohol and recovered gas. The recovered gas is compressed and then mixed with the compressed mixed gas through a pipeline for recycling;

[0131] Step 4: The crude alcohol is transported to a distillation tower at a refining temperature of 80° C. and a pressure of 0.6 bar, and distilled to obtain methanol and production waste liquid.

[0132] Comparative Example 1

[0133] The difference between this comparative example and Example 6 is that, in the preparation process of the catalyst filler used, in step S1, no copper acetate solution is added.

[0134] Comparative Example 2

[0135] The difference between this comparative example and Example 6 is that, in the preparation process of the catalyst filler used, step S2 is omitted, and no indium-containing co-precipitated metal is added in step S4.

[0136] Comparative Example 3

[0137] The difference between this comparative example and Example 6 is that, in the preparation process of the catalyst filler used, in step S3, nicotinic acid is not added to the nicotinic acid solution.

[0138] Comparative Example 4

[0139] The difference between this comparative example and Example 6 is that, in the preparation process of the catalyst filler used, step S4 is omitted, and the modified mixed powder in step S5 is replaced by the mixed powder in step S3.

[0140] Performance Test:

[0141] The specific surface area and porosity of the catalyst fillers used in Examples 4-6 and Comparative Examples 1-4 were tested with reference to the standard GB / T 21650.1-2008 "Mercury Intrusion Porosimetry and Gas Adsorption Method for Determination of Pore Size Distribution and Porosity of Solid Materials Part 1: Mercury Intrusion Porosimetry";

[0142] The synthesis gas after the reaction was introduced into a gas chromatograph for online detection and analysis, and then the conversion rate of carbon dioxide and the selectivity of methanol in Examples 4-6 and Comparative Examples 1-4 were tested according to Formula 1 and Formula 2 respectively;

[0143] Formula 1: ;

[0144] Formula 2: ;

[0145] Where: , is the chromatographic peak area of ​​carbon dioxide gas in the synthesis gas; For methanol and CO 2 The relative correction factor between is the chromatographic peak area of ​​methanol gas in the synthesis gas, For CO and CO 2 The relative correction factor between is the chromatographic peak area of ​​CO in the synthesis gas, For methane and CO 2 The relative correction factor between is the chromatographic peak area of ​​methane gas in the synthesis gas, For ethanol and CO 2 The relative correction factor between is the chromatographic peak area of ​​ethanol gas in the synthesis gas. The specific test results are shown in Table 1 below.

[0146] Table 1-Performance test data of the sample

[0147] Data Analysis:

[0148] Comparative analysis of the data in Table 1 above shows that the specific surface area of ​​the catalyst filler prepared by the present invention reaches 853 m 2 / g, the porosity reaches 72.4%, and the catalyst filler is used to catalyze the hydrogenation of carbon dioxide to produce methanol, the carbon dioxide conversion rate reaches 14.9%, and the selective output of methanol reaches 95.4%, and all performance parameters are better than the comparative example;

[0149] Data description:

[0150] The present invention optimizes the preparation of modified molybdenum disulfide, indium-containing co-precipitated metal and porous carbon powder, and coats and modifies them, thereby effectively improving the specific surface area and porosity of the catalyst filler and improving the conversion rate of carbon dioxide and its selectivity for conversion to methanol in the process of preparing methanol by hydrogenation of carbon dioxide.

[0151] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing methanol by hydrogenating carbon dioxide, characterized in that: The following steps are involved: S1, mixing carbon dioxide and hydrogen and compressing them to obtain a compressed mixed gas; S2, filling the catalyst filler into the methanol synthesis tower; The compressed mixed gas is heated and then transported to a methanol synthesis tower, and after catalytic synthesis, it is discharged from the top of the methanol synthesis tower to obtain synthesis gas, wherein the catalyst filler is a mixed powder composed of modified molybdenum disulfide, indium-containing co-precipitated metal and porous carbon powder as a base material, which is obtained by chemical modification and sol granulation, and then calcined and formed; S3, after heat exchange and cooling, the synthesis gas enters the separator to separate methanol and water in the mixed gas to obtain crude alcohol and recovered gas, which is then compressed and mixed with the compressed mixed gas for recycling; S4, the crude alcohol is transported to a distillation tower for distillation to obtain methanol and production waste liquid; The catalyst filler is processed by the following steps: A1. Add modified molybdenum disulfide, indium-containing co-precipitated metal and porous carbon powder into a ball mill, and pass through a 200-mesh sieve after ball milling to obtain a mixed powder; A2, adding the mixed powder and emulsion into a reactor, stirring for 30-50 min, adding phloroglucinol, formaldehyde solution, tetraethyl orthosilicate and ammonia water into the reactor, raising the temperature of the reactor to 55-65° C., keeping the temperature for reaction for 20-22 h, and post-treating to obtain a modified mixed powder, wherein the emulsion is composed of anhydrous ethanol, purified water, hexadecyltrimethylammonium bromide and polyethylene glycol 200 in a dosage ratio of 50 mL: 30 mL: 3 g: 1 g; A3, adding the modified mixed powder, sodium aluminate, silica sol, starch, dispersant and deionized water into a reactor, stirring and dispersing at room temperature for 20-30 minutes, adding the sodium alginate solution into the reactor, stirring at this temperature for 20-30 minutes, and obtaining a mixed solution; A4, the mixed liquid is granulated and solidified to obtain a catalyst filler; Granulation and curing includes the following steps: B1, adding the mixed solution dropwise to the calcium chloride solution, curing for 60-80 minutes, and post-processing to obtain a catalyst filler body; B2. Place the catalyst filler blank in a nitrogen-protected tubular furnace, and perform calcination in the tubular furnace according to the program to obtain the catalyst filler. The preparation method of modified molybdenum disulfide is as follows: ammonium molybdate, thiourea and deionized water are added to a reactor and stirred, the temperature of the reactor is increased to reflux, a copper acetate solution is added to the reactor, the reaction is carried out at a temperature of 22-24 hours, and modified molybdenum disulfide is obtained by post-processing; The preparation method of the indium-containing co-precipitated metal is as follows: zinc nitrate, indium nitrate and deionized water are added to a reactor and stirred until the system is dissolved, a sodium carbonate solution is added dropwise to the reactor, the pH of the system is adjusted to 8.8-9.2, the temperature of the reactor is increased to 70-75°C, the reaction is stirred for 3-5 hours, the temperature of the reactor is decreased to 45-55°C, the reaction is aged for 6-8 hours, and the indium-containing co-precipitated metal is obtained by post-treatment, wherein the amount ratio of zinc nitrate, indium nitrate and deionized water is 1g:3g:50mL; The porous carbon powder is obtained by the following steps: C1. Add nicotinic acid solution and chitosan into a reactor and stir. The temperature of the reactor is raised to 60-70° C. and stirred for 10-12 hours. Post-treatment is performed to obtain modified chitosan, wherein the nicotinic acid solution is composed of nicotinic acid, zinc chloride and deionized water in a dosage ratio of 1 g:5 g:30 mL. C2, placing the modified chitosan mixture in a nitrogen-protected tubular furnace, raising the temperature of the tubular furnace to 600-650°C, maintaining the temperature for 120-160 minutes, cooling and discharging the material to obtain a porous carbon powder crude product; C3. Add the crude porous carbon powder and the activation solution into a reactor, stir at room temperature for 6-8 hours, and perform post-treatment to obtain porous carbon powder, wherein the activation solution is 0.8-1.2 mol / L hydrochloric acid.

2. The method for preparing methanol by hydrogenating carbon dioxide according to claim 1, characterized in that: In step A1, the weight ratio of the modified molybdenum disulfide, the indium-containing co-precipitated metal and the porous carbon powder is 5-7:2-3:6-8; in step A2, the amount ratio of the mixed powder, emulsion, phloroglucinol, formaldehyde solution, tetraethyl orthosilicate and ammonia water is 10g:200mL:5g:10g:30-40g:2-3g:6-8mL, the mass content of the formaldehyde solution is 28-35%, and the mass content of the ammonia water is 15-25%; in step A3, the amount ratio of the modified mixed powder, sodium aluminate, silica sol, starch, dispersant, deionized water and sodium alginate solution is 5g:4-6g:60-70g:12-15g:2-3g:200mL:40mL, the dispersant is sodium dodecyl sulfate, and the sodium alginate solution is composed of sodium alginate and deionized water in an amount ratio of 1g:50mL.

3. The method for preparing methanol by hydrogenating carbon dioxide according to claim 1, characterized in that: In step B1, the concentration of the calcium chloride solution is 0.2-0.3 mol / L; in step B2, the process of programmed roasting is: the temperature is increased to 110-120° C. at a heating rate of 5-8° C. / min in a tubular furnace, and kept warm for 30-50 min; the temperature is increased to 220-260° C. at a heating rate of 2-4° C. / min in a tubular furnace, and kept warm for 40-60 min; the temperature is increased to 430-450° C. at a heating rate of 3-5° C. / min in a tubular furnace, and kept warm for 50-60 min, and then naturally cooled to room temperature.

4. The method for preparing methanol by hydrogenating carbon dioxide according to claim 1, characterized in that: The usage ratio of the ammonium molybdate, thiourea, deionized water and the copper acetate solution is 1g:4g:25mL:3g, and the copper acetate solution is composed of copper acetate and deionized water in a weight ratio of 1:

4.

5. The method for preparing methanol by hydrogenating carbon dioxide according to claim 1, characterized in that: In step C1, the ratio of chitosan to nicotinic acid solution is 1 g:20 mL; in step C3, the ratio of porous carbon powder crude product to activation solution is 1 g:30-50 mL.

Citation Information

Patent Citations

  • Catalyst for synthesizing methanol through hydrogenation of carbon dioxide

    CN110833843A

  • A process for the production of porous inorganic materials or a matrix material containing nanoparticles

    CN1735562A

  • Bio-assisted process for conversion of carbon-dioxide to fuel precursors

    EP3536798A1